What is a Fence? - Parfitt, Mark; Kickett, Rohin (Nillumbik Shire Council, 2023)
What is a Fence? is a collaborative video artwork by Noongar artist Rohin Kickett and Mark Parfitt designed to reveal an Aboriginal/Settler perspective of place. With a monologue overlaying video montage of suburban Perth (Boorloo), Kickett speaks about the traditional ecology, stolen land, and trauma felt from colonisation and segregation. Both artists look to the future, working together on unceded Noongar land by encouraging mutual respect and learning the history and stories present in the suburbs of Perth (Boorloo).